The Bidirectional Link Between RNA Cleavage and Polyadenylation and Genome Stability: Recent Insights From a Systematic Screen - Spada, Stefano; Luke, Brian; Danckwardt, Sven (Frontiers in Genetics, 2022)
The integrity of the genome is governed by multiple processes to ensure optimal survival and to prevent the inheritance of deleterious traits. While significant progress has been made to characterize components involved in the DNA Damage Response (DDR), little is known about the interplay between RNA processing and the maintenance of genome stability. Here, we describe the emerging picture of an intricate bidirectional coupling between RNA processing and genome integrity in an integrative manner. By employing insights from a recent large scale RNAi screening involving the depletion of more than 170 components that direct (alternative) polyadenylation, we provide evidence of a bidirectional crosstalk between co-transcriptional RNA 3’end processing and the DDR in a manner that optimizes genomic integrity. We provide instructive examples illustrating the wiring between the two processes and show how perturbations at one end are either compensated by buffering mechanisms at the other end, or even propel the initial insult and thereby become disease-eliciting as evidenced by various disorders.